Narrativas de indução pedagógica na alfabetização e o podcast Vozes Docentes: uma conversa entre a ilha do Marajó e Belém do Pará - SILVA, Jessika de Assiz da (Universidade Federal do Pará, 2025)
Narrating oneself during training in pedagogical induction, within the field of literacy, means perceiving oneself in the midst of the self, others and training. Experiencing formative paths with teacher authorship and a theoretical basis, immersed in school reality, was challenging in this life-research-training trajectory. A subjective, collective and unrepeatable dive into living the experience in an autobiographical, narrative and Larrosian way. Thus, I wove this conversation between the island of Marajó (Salvaterra) and Belém do Pará through an Amazonian narrative, experienced in the process of pedagogical induction in literacy. This journey followed the course of the river of the creative narrative research writing methodology (Lucio, 2020), which converges at its source the autobiographical dimension, at its mouth the fictional dimension and on its bank the self-formative dimension. I entangled this work with my Marajoara autobiography; the fictional one of a girl and a literacy teacher from the 1960s and the self-formative one in the research on pedagogical induction. A transfluence of the narrator, literacy teacher and researcher who finds herself with training in a field that is still little studied: teacher induction and the podcast, as a pedagogical resource that has enhanced the training of Pedagogy undergraduates. My aim with this trip was to build a podcast as a formative educational product of pedagogical induction in literacy. In order to navigate Guajará Bay on the shores of the Federal University of Pará, in the waters of the Amazon, my methodology was based on narrative research (Clandinin; Connely, 2015). On this voyage, important crew members are boarding the ship. In the bow are our theoretical references: Clandinin and Connelly (2015), Lucio (2016, 2020), Nogaro, Kuhn and Moreira (2021), Larrosa (2002), Suarez (2017), Smolka (2012) and Santos (2014). The authors are the subjects of the research: students on the Pedagogy course at the Federal University of Pará, immersed in the UFPA School of Application, located in Belém. To build the data that fueled this ship, on the port side we have a systematic review of the literature over 10 years, on the starboard side we have the development of a pilot induction project, and in the hold we have the analysis of letters as narrative pedagogical documentation and in the hatch we have the Vozes Docentes podcast. In view of this, the hull of this ship (our considerations) shows that, when mediating a training process in pedagogical induction, through the podcast, I have to take a political, epistemological and methodological stance, in which I consider the subjects as inventive authors of their cultural history from their own voices. It's not talking about, it's talking with. Throughout the pedagogical induction process involved in the social reality of the Amazonians, which is based on experience as that which touches us and runs through us, the voices written in the letters – which I transpose into the voices spoken in the podcast – emphasize experience, alterity, affectivity and the student-teacher-student relationship as substantial premises for the student's formation within pedagogical induction in literacy.